Infectious Pancreatic Necrosis Virus Causing Clinical and Subclinical Infections in Atlantic Salmon Have Different Genetic Fingerprints - Mutoloki, Stephen; Jøssund, Trude B.; Ritchie, Gordon; Munang'andu, Hetron M.; Evensen, Øystein (Frontiers in Microbiology, 2016)
Infectious pancreatic necrosis virus (IPNV) is the causative agent of IPN, an important disease of salmonids. IPNV infections result in either sub-clinical or overt disease and the basis of this difference is not well-understood. The objective of the present study was to determine the VP2 gene of the virus associated with the different forms of clinical manifestation. Groups of Atlantic salmon (Salmo salar L.) reared in farms located in different IPN disease pressures were monitored from brood stock until grow-out over a 3 year period. Hatcheries A1 and B1 as well as cooperating seawater farms were located in a low disease risk area while hatcheries A2 and B2 as well as their cooperating seawater farms were in high IPN risk areas. Samples including eggs, milt, whole fry, kidney depending on the stage of production were collected during outbreaks or in apparently healthy populations where no outbreaks occurred. The virus was re-isolated in CHSE cells and the VP2 gene amplified by RT-PCR followed by sequencing. During the freshwater stage, there were no disease outbreaks at hatcheries A1, A2, and B1 (except in one fish group that originated from hatchery B2), although IPNV was isolated from some of the fish groups at all 3 hatcheries. By contrast, all fish groups at hatchery B2 suffered IPN outbreaks. In seawater, only groups of fish originating from hatchery A1 had no IPN outbreaks albeit virus being isolated from the fish. On the other hand, fish originating from hatcheries A2, B1, and B2 experienced outbreaks in seawater. The VP2 amino acid fingerprint of the virus associated with subclinical infections from A1 and co-operating seawater sites was V64A137P217T221A247N252S281D282E319. By contrast, all virus isolates associated with clinical infections had the motif I64T137T217A221T247V252T281N282A319, where underlined amino acids represent the avirulent and highly virulent motif, respectively. Phylogenetic analysis of amino acid sequences showed 2 clades, one of isolates associated with subclinical infections (from A1 and cooperating seawater farms) and the other of isolates from fish with overt disease (all other sites). Furthermore, the clustering pattern of isolates suggests more circulation of virus within fish groups rather than between them.